2014
DOI: 10.1038/aps.2014.93
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of mGluR5 in the nucleus accumbens shell but not core attenuates heroin seeking behavior in rats

Abstract: Aim: Glutamatergic neurotransmission in the nucleus accumbens (NAc) is crucial for the relapse to heroin seeking. The aim of this study was to determine whether mGluR5 in the NAc core or shell involved in heroin seeking behavior in rats. Methods: Male SD rats were self-administered heroin under a fixed-ratio 1 (FR1) reinforcement schedule for 14 d, and subsequently withdrawn for 2 weeks. The selective mGluR5 antagonist 2-methyl-6-phenylethynyl-pyridine (MPEP, 5, 15 and 50 nmol per side) was then microinjected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 44 publications
(64 reference statements)
1
11
0
Order By: Relevance
“…Our data add to the existing evidence for an association between the central mGlu 5 R and MOP systems ( Schroder et al, 2009 ; Akgun et al, 2013 ; Smeester et al, 2014 ). Indirect evidence further suggests a possible modulatory inter-play between mGlu 5 R and MOPr systems in the striatum to regulate opioid-related behaviors, since intra-Acb administration of an mGlu 5 R antagonist attenuated the acquisition of morphine CPP ( Roohi et al, 2014 ), and intra-AcbSh, but not intra-AcbC, administration of an mGlu 5 R antagonist attenuated both cue- and priming-induced reinstatement of heroin-seeking behavior in rats ( Lou et al, 2014 ). The exact neurobiological mechanism underlying the observed mGlu 5 R upregulation in the MOPr knockout mice remains unclear, since glutamate content and/or release in the brain of MOPr knockout mice have not been evaluated so far.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our data add to the existing evidence for an association between the central mGlu 5 R and MOP systems ( Schroder et al, 2009 ; Akgun et al, 2013 ; Smeester et al, 2014 ). Indirect evidence further suggests a possible modulatory inter-play between mGlu 5 R and MOPr systems in the striatum to regulate opioid-related behaviors, since intra-Acb administration of an mGlu 5 R antagonist attenuated the acquisition of morphine CPP ( Roohi et al, 2014 ), and intra-AcbSh, but not intra-AcbC, administration of an mGlu 5 R antagonist attenuated both cue- and priming-induced reinstatement of heroin-seeking behavior in rats ( Lou et al, 2014 ). The exact neurobiological mechanism underlying the observed mGlu 5 R upregulation in the MOPr knockout mice remains unclear, since glutamate content and/or release in the brain of MOPr knockout mice have not been evaluated so far.…”
Section: Discussionmentioning
confidence: 99%
“…With respect to opioids, pharmacological blockade of the mGlu 5 R attenuated the development of tolerance to morphine ( Kozela et al, 2003 ; Gabra et al, 2008 ), inhibited the expression of morphine locomotor sensitisation ( Kotlinska and Bochenski, 2007 ), prevented the acquisition ( Roohi et al, 2014 ) and expression of morphine place-preference ( Popik and Wrobel, 2002 ; Aoki et al, 2004 ; Herzig and Schmidt, 2004 ; Veeneman et al, 2011 ), and decreased morphine self-administration ( Brown et al, 2012 ) in rodents. In addition, administration of the mGlu 5 R antagonist, 3-((2-Methyl-4-thiazolyl)ethynyl)pyridine (MTEP), decreased cue-induced reinstatement of morphine seeking in mice ( Brown et al, 2012 ), and intra-nucleus accumbens shell (AcbSh) administration of the mGlu 5 R antagonist 2-Methyl-6-(phenylethynyl)pyridine (MPEP) decreased heroin-seeking induced by context, cues, or heroin priming in rats ( Lou et al, 2014 ). Moreover, mGlu 5 R antagonism has been found to potentiate the antinociceptive effects of morphine in rats ( Picker et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, glutamatergic dysregulation is implicated in the etiology of both addiction (reviewed in Cleva and Olive, 2012; Holmes et al, 2013; Kalivas et al, 2009; Tsai et al, 1995) and anxiety (reviewed in Bergink et al, 2004; Simon and Gorman, 2006; Swanson et al, 2005). Not only do mGlu5 receptor antagonists attenuate behavioral measures of both drug seeking and anxiety in animal models (e.g., Backstrom et al, 2004; Cozzoli et al, 2009, 2012, 2014; Klodzinska et al, 2004; Kumar et al, 2013; Lou et al, 2014; Sinclair et al, 2012), but they have also shown anxiolytic efficacy in human clinical trials (Pecknold et al, 1982; Porter et al, 2005) and mGlu5 antagonism is thought to contribute to the therapeutic efficacy of the alcoholism medication Acamprosate (De Witte et al, 2005; Harris et al, 2002; Mann et al, 2008). Thus, a mutual basis of glutamatergic dysfunction could contribute to the high comorbidity between addiction and affective disorders.…”
Section: Introductionmentioning
confidence: 99%
“…The AcbSh is a component of the extended amygdala macrocircuit ( Alheid, 2003 ), the dysregulation of which is theorized to be a critical driver of the negative reinforcing properties of alcohol (e.g., Gilpin and Koob, 2008 ; Tunstall et al, 2017 ). Given that: (1) mGlu5 expression is up-regulated during withdrawal from binge-drinking ( Cozzoli et al, 2012 ; Lee et al, 2016 ); (2) inhibiting AcbSh activity produces an anxiolytic effect ( Lopes et al, 2012 ) and (3) mGlu5 inhibition within the AcbSh reduces signs of opioid withdrawal-induced anxiety ( Radke and Gewirtz, 2012 ; Lou et al, 2014 ), the present study tested for a cause-effect relation between the coincident increase in AcbSh mGlu5 expression and hyper-emotionality during binge-alcohol withdrawal ( Lee et al, 2016 , 2017c ). For this, mice with a history of binge-drinking during either adolescence or adulthood were infused intra-AcbSh with the mGlu5 negative allosteric modulator 3-[(2-Methyl-1,3-thiazol-4-yl)ethynyl]pyridine (MTEP) at a time post-alcohol consumption when adult- and adolescent-onset drinking mice exhibit robust behavioral signs of negative affect (i.e., during early and protracted withdrawal, respectively; Lee et al, 2016 , 2017b , 2018 ).…”
Section: Introductionmentioning
confidence: 99%